[Rezension von: Celador Angón, Óscar, 1969-, Entidades locales y libertad religiosa] - Gallardo, Mercedes Vidal (Revista española de derecho canónico, 2023)
Review of the book by ÓSCAR CELADOR ANGÓN in which he addresses issues of extraordinary topicality with the rigor that presides over his long research career. The monograph is written from the clarity of ideas from a rich bibliographical selection, consisting not only of legislative texts but also other doctrinal and jurisprudential sources.